ANALISIS SEMANTIK TERHADAP PENGGUNAAN BAHASA TERSELUBUNG DALAM KASUS NARKOTIKA: STUDI LINGUISTIK FORENSIK PADA PERNYATAAN TEDDY MINAHASA - Zamil, Naila Salsabila; Irwan Suswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of language in a legal context through a forensic linguistics approach to statements made by Teddy Minahasa in the narcotics case that ensnared him. This study focuses on semantic analysis using a contextual semantic approach referring to Contextual Semantics Theory, an approach that understands the meaning of utterances based on the context of the situation, the relationship between speakers, and the background of the speech event. The research data was obtained from various accountable sources, including WhatsApp conversation transcripts found on witness Linda Pujiastuti's cell phone that were spread in online media coverage, as well as video recordings of interviews and trials related to the case. The data were analyzed to identify the meaning of utterances, word choice, and the context of language use in communication related to the legal case. The results of the study indicate that the meaning of utterances in the analyzed statements is influenced by the communication context and the underlying legal situation. This finding confirms that a contextual semantic approach in forensic linguistics is important to use to understand the meaning of language more comprehensively so that it can support a more objective interpretation of language evidence in a criminal case.